Ketebalan Daun dan Laju Transpirasi Pada Tanaman Hias Dikotil - Yuliana Ovan Dacosta; Entin Daningsih (Institut Pertanian Bogor, 2022)
Transpiration rate internally depends on the water content that occupies the tissue in the leaves, which is reflected in the thickness of the leaves. This study measured the transpiration rate and leaf thickness of ornamental dicotyledon plants. The experiment used Factorial Completely Randomized Design (CRD) with three replications. Six species of dicotyledon plants and three parts of the plant were the main factors. The interaction between plant species and plant parts was a combination factor. The transpiration rate was measured using a weighing method and leaf thickness was measured from the upper to the lower epidermis. Leaf thickness was measured before and after transpiration rate measurement. Data were analyzed using SAS with Factorial CRD model and continued with the LSD test if there was a significant treatment. The species of plant and plant parts had significant effects on the transpiration rate and leaf thickness, but the combination or interaction of the two did not affect the transpiration rate and leaf thickness. Aerva sanguinolenta Bi. had the highest transpiration rate followed by Syzygium paniculatum Gaertn., Tabernaemontana divaricata (L.) R. Br. ex Roem. & Schult., Excoecaria cochinchinensis Lour., Bougainvillea glabra Choisy, and Codiaeum variegatum (L.) A. Juss while the leaves at the bottom of the plant had the highest transpiration rate compared to the middle and upper parts of the plant. Codiaeum variegatum (L.) A. Juss. had thick leaves and less transpiration rate than the other plants. The leaves at the top had a higher thickness than those at the middle and bottom parts of the plant. This occurs because the transpiration rate of the lower leaf was faster than the upper and middle parts. Leaf thickness was inversely correlated to the rate of transpiration. Keywords: dicotyledon, leaf thickness, transpiration rate